Species identification of Candida isolates obtained from oral lesions of HIV infected patients - Baradkar V; Kumar S (Wolters Kluwer Medknow Publications, 2009)
A total of 60 patients suspected to have AIDS with oral lesions suggestive of oral candidiasis were studied. Candida species were isolated from 50 patients. Candida albicans was the commonest isolate (70 %) followed Candida parapsilosis (15%), Candida glabrata (7.5%) and Candida tropicalis (5%) respectively. Candida dubliniensis was isolated from a single case only. Though the reports from developed countries show more prevalence of the novel species Candida dubliniensis, in our study it was isolated in a single case. All the patients were treated successfully with oral fluconazole for 7 days except for the patients from which Candida glabrata was isolated, who were treated with Amphotericin B.